Managing the difficult airway: A survey of doctors with different seniority in China. Issue 38 (24th September 2021) - Liu, Hui-Hui; Wang, Yong; Zhong, Ming; Li, Yu-Hui; Gao, Huan; Zhang, Jian-Feng; Ma, Wu-Hua
Abstract : Abstract: Although equipment and human resources are vital elements of difficult airway management (DAM). But the approach and practice of DAM are more important. So, we conducted the present survey to address anesthesiologists of different working years in this knowledge gap. This nationwide cross-sectional study was conducted from October 27, 2016 to November 27, 2016. The survey was completed online in New Youth Anesthesia Forum including DAM assessment, anticipated and unanticipated DAM, difficult airway algorithm, use of the front of neck access (FONA) technique and training, DAM outside the operation room, and difficult extubation management. We received 1935 replies (44%). Mouth opening and Mallampati classification were the most common methods to evaluate difficult airways. When suffering from unanticipated difficult airway 63% less than 10 years anesthesiologists (LA) and 65% more than 10 years anesthesiologists (MA) would ask for help after trying 1 to 2 times ( P  = .000). More than 70% of LA and MA respondents reported preferring cannula cricothyrotomy to deal with emergency airway, 507 (41.6%) MA respondents reported that they used FONA techniques to save patients' lives ( P  = .000). Nearly 70% respondents worried full stomach when intubated outside operation room and more than 80% respondents selected auscultation to identify the placement. More than 80% respondents had not used Bougie to assist extubation. A 73.2% respondents know ABS algorithm and 96.4% know Chinese airway expert consensus among MA respondents, this was significant to LA respondents ( P  = .000). The respondents in the LA and MA have a training gap in their evaluation of difficult airways, trained and used FONA emergency skills, facilitated of the airway guidelines at home and abroad. Also, we should provide more airway theory and skill training to our young doctors to advanced airway skills.